Quality of service aware contention and deployment quality analysis in multimedia wireless sensor networks - Dönmez, Mehmet Yunus. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Emerging multimedia applications for wireless sensor networks (WSN) require the co-existence of different types of traffic with different quality of service (QoS) provisions in terms of latency and throughput. Prioritization based service differentiation mechanisms are applied in all layers of communication to satisfy the QoS requirements of each traffic class. The prioritization in contention is one of the differentiation methods applied in the medium access layer. In this thesis, we propose an analytical model for the contention latencies and energy expenditures of different classes in a prioritized contention structure consisting of contention partitions allocated to priority classes. In the analysis, we explore the optimum sizes of these partitions in terms of contention latency and the total energy expenditure in the neighborhood for each priority class. This analytical model is also useful for the evaluation of various recent contention prioritization schemes in WSNs. We adapt this generic analysis to SMAC protocol which introduces the low-duty-cycle operation for energy efficiency. We explore the effects of the duty cycle, the contention window size and the data size on the performance of networks with single and multiple types of traffic. Apart from the communication based QoS, the sensing quality of the network brings about another perspective to the QoS in WSNs regarding the quality of the deployment. We provide a theoretical analysis which derives a quality measure for the deployment in terms of network parameters accounting the loss of sensors or loss of communication due to jamming.
Keywords: Wireless sensor networks.; Quality function deployment.